Stereoselective Approaches to β-Linked 2-Deoxy Sugars - Clay S. Bennett (Molecules)
This review presents a survey of recent developments in the synthesis of β-linked 2-deoxy sugars. Approaches ranging from catalysis to de novo synthesis are described, with a focus on methods developed in the last 10 years. Where relevant, the application of these technologies to synthesis and mechanistic information is discussed. Finally, it concludes with an examination of the scope and limitations of these technologies, as well as examinations about where the field should head next.